Phytochemical Analysis and in vitro Evaluation of Anti-Inflammatory and Thrombolytic Activities Using Fractional Crude Extracts Derived from Six Medicinal Plants from Chittagong Hill Tracts of Bangladesh (Journal of Bio-Science, 2026)
The ethnic people of Chittagong Hill Tracts in the southern region of Bangladesh use Ardisia paniculata, Ardisia solanaceae, Argyreia capitiformis, Diplazium splendens, Ixora finlaysoniana, and Pouzolzia sanguinea to alleviate fever, diarrhea, cough, dysentery, inflammation, insomnia, and analgesia. However, there is no scientific evidence regarding the bioactivity of these plants. This study aimed to explore phytochemicals, in vitro anti-inflammatory and thrombolytic activities using phytochemical qualitative analysis, protein denaturation and clot disruption methods. The extracts were prepared using a Soxhlet extractor with methanol and further fractionated with ethanol, chloroform, and n-hexane. The phytochemical evaluation indicates alkaloids, glycosides, amides, phenols and vitamins present in ethanol fractions of all medicinal plants. The anti-inflammatory activity of the ethanol extract of P. sanguinea   showed better activity compared to other studied medicinal plants. The ethanol fraction  exhibited the highest inhibition of protein denaturation (62.52%), followed by n-hexane (59.67%) and chloroform (49.43%) at 160 µg/mL of P. sanguinea in in vitro anti-inflammatory test. The IC50 values for P. sanguinea were 114.50 µg/mL, 129.09 µg/mL, and 150.17 µg/mL, which were lower than other medicinal plants in the anti-inflammatory test. Acetylsalicylic acid, used as a positive control, demonstrated 82.29% effectiveness at similar dosages, with an IC50 value of 79.39 µg/mL. The chloroform fraction of I. finlaysoniana showed moderate clot lysis (55.43%) compared to positive control streptokinase (80.31%) and other medicinal plants. Furthermore, this study revealed that the ethanol fraction of P. sanguinea leaves is more potent  and it showed anti-inflammatory activity, while chloroform fraction of I. finlaysoniana  leaves  showed more clot lysis activities compared to other studied medicinal plants.  This study opens new insights into pharmacological potential of Bangladeshi medicinal plants, which might be useful for developing cost-effective, plant -based medicine to protect chronic inflammation and cardiovascular diseases.J. Bio-Sci. 33(1): 21-30, 2025